A avaliação do efeito de antissépticos na superfície ocular e o papel da gentamicina no controle microbiano de córneas doadas - Ito, Célia Regina Malveste (2017)
Decontamination of the surface of the donor eyeballs is part of the operational norms that eye banks advocate before preservation, and antisepsis procedures are effective, ensuring greater transplantation safety. The objective of the present study was to evaluate the antiseptic effect in reducing the microbiota of the ocular globe of donors of corneas prior to enucleation, with 5% povidone-iodine (PVP-I) and 0.05% chlorhexidine gluconate (GC), In the action times of 5, 10 and 15 minutes, as well as the susceptibility profile of the microbiota isolated from gentamicin. Thirty pairs of corneas received antiseptics, with PVP-I in the right eye and GC in the left, and for each time of action 10 pairs of eyeballs were used. Swabs were collected from the ocular surface before application of the solutions, after and at the time of preservation of the corneal tissue, to evaluate the reduction of the microbiota. After identification of the microbiota, an antibiogram test was performed with gentamicin. The data were computed and evaluated by Chi-square or Fisher's exact test, T-test and McNemar test paired, and the statistical significance level was 5% (p <0.05). In the second collection, after antisepsis, there was a reduction of 39,5% in the total of gram positive bacteria (G +), and of 76,5% in the gram negative (G-) bacteria, with no statistically significant difference (p = 0.183), which demonstrated that the bacterial elimination capacity of the antiseptics was similar. It was observed that, in the second collection, both were more effective for G-, with a statistically significant difference (p <0.001), than for G +, with no statistically significant difference (p = 0.494). In the third collection, after the residual effect of the antiseptics, there was a reduction of 99.1% of all the microorganisms. In the antibiogram test, 88% of the isolated microorganisms were sensitive to gentamicin. It was concluded that the use of antiseptics is essential for the effective decontamination of donated corneas prior to preservation. The residual time of the antiseptics increased the decontamination power of PVP-I and GC, being similar in reducing the microbiota of the ocular globe of the donor of corneas. Gentamycin contained in the cornea preservation medium complements the antisepsis of the donated tissues.